Technology and Mental Health: A study on workers in management posts - Michaelsen Macedo, Jaqueline; Giongo, Carmem Regina (Revista de Psicologia, 2023)
This study aims to understand the interfaces between technology, work, and mental health on people in management positions. This research of exploratory-descriptive nature used a mixed methodology and involved the participation of 85 workers. An online self-administered questionnaire was used as an instrument for collecting data, and the results were analyzed qualitatively through thematic analysis and quantitatively using simple statistics. The results showed that 60% of the participants stated that they continue to interact of the work affairs outside office hour, 71.8% check the messages of work on their days off and in the pandemic the disconnection time decreased to 44.71% of them. The overall conclusions were that the consequences, possibly, of this exposure are associated with the connection time that workers are required to have with the use of technology, favoring their full availability and leading to an increasing feeling of response being mandatory, anxiety and constantly alert.